Pendampingan Pengajian Kitab Sairu Al-Salikin Bab tentang I’tiqad (Keyakinan) bagi Jamaah Masjid Al-Mushlihat Kecamatan Tembilahan - Abd. Syahid; Syamsiah Nur; Moh. Sain; M. Ilyas; Kamaruddin Kamaruddin (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Sairu Al-Salikin, the book defines as the footsteps of the Salik (seekers) in worshiping the God of the universe. It is one of the classic books by a great scholar of the 18th-century archipelago in Indonesia, precisely from Palembang written by Sheikh Abdus Shamad Ibn Abd Al -Rahman Ibn Abd Al-Jalil Al-Palimbani Al-Jawi known as Sheikh Abdus Shamad Al-Palimbani. The book consists of four chapters and discusses the science of monotheism, fiqh, and mysticism. This Malay-translation book is from the Ihya Ulumuddin; a very famous book by Al-Imam Al-Ghazali. While the discussion in this study was the Essence of Allah SWT and all His Attributes both the Nature of Salabiah, the Nature of Tanziah and the Nature of Wujudiyah the Nature of Tsubutiyah and His Af’al.